State-of-the-art carbon metering: Continuous emission monitoring systems for industrial applications - Ning Ding; Yanheng Xi; Wenting Jiang; Hongwei Li; Jun Su; Sixiang Yang; Tek Tjing Lie (Heliyon)
In response to the urgency of climate change, nations are enforcing stricter regulations on emissions, particularly in the energy sector, intensifying the focus on precise carbon measurement. This review systematically examines carbon emission scenarios by analyzing energy system structures and advancements in monitoring and metering technologies. We introduce the concept of real-time, dynamic carbon metering, which enhances carbon accounting accuracy through context-specific measurements. Emphasizing key technologies for Continuous Emission Monitoring Systems (CEMS) in stationary sources, this paper highlights innovations in sensor technology, such as NDIR and nanotechnology-enabled sensors, that improve detection sensitivity and reliability. Key challenges for CEMS implementation are identified, including high costs and regional variations in emission standards. Through a bibliometric analysis using CiteSpace, we reveal emerging trends in integrated gas monitoring, real-time data analytics, and the role of artificial intelligence in refining data interpretation. Our findings underscore the need for policy-related frameworks that incentivize technological innovation, facilitating the development of cost-effective and adaptable monitoring solutions to support accurate, actionable carbon data for effective emissions management and alignment with global environmental goals.